Kebijakan Kriminal dalam Upaya Penanggulangan Tindak Pidana Bisnis Live Sex - Randy Pradityo (Jurnal Hukum IUS QUIA IUSTUM, 2015)
The impacts of new criminal acts containing pornography such as the criminal act of live-sex business are very dangerous in the life of a nation and country in general, as well as the young generation in particular. In relation to that, the problem in this research is about the criminal policies as an effort to tackle the criminal act of live-sex business in the present and in the future. This was a legal normative (doctrinal) research. The finding concludes that the criminal policies related to the criminal act of live-sex business are not explicitly governed by Pornography Law. However, there are several articles which are very close to such thing: Article 34 for the subjects and actors of live sex, and Article 35 for the viewers of live sex. The RUU KUHP (the draft of criminal law) accommodates the sanctions of the criminal act of live-sex business, but it does not govern it explicitly. Such thing can be seen in Article 469, Article 473, and Article 475 for the subjects; Article 472 and Article 474 for the viewers of live-sex scenes. In addition, non-penal policies, such as socialization and a good approach, are also necessary in order to make the efforts successful.